Life table and demographic parameters of rice leaffolder Cnophalocrocis medinalis Guenee (Lepidoptera:Pyralidae - Roseli, Marina; Adam, Nur Azura; Lau, Wei Hong; Yaakop, S. (Universiti Kebangsaan Malaysia, 2019)
Rice leaffolder, Cnaphalocrocis medinalis is important pest species and become a major threat to rice production in many Asian countries including Malaysia. A range of 30 to 80% of rice yield losses was assessed from severely damage fields under epidemic situation in India. Cnaphalocrocis medinalis has history of outbreak in Sekinchan, Selangor in early 1980’s. Understanding the biology and factors that could be manipulated for its control are very limited. Life table and demographic parameters play important role in determining the key factors that responsible for the highest mortality within population. Therefore, the objective of our study was to construct life table and demographic parameters of C. medinalis. A survivorship and fecundity study of C. medinalis was conducted in laboratory (27.2±0.48 °C, 78.4±1.64% RH and 12:12h photoperiod) using three cohorts consisted of 102, 103 and 105 one-day old eggs. The survival and mortality of every life stage were observed and recorded daily. Nine pairs of one-day old C. medinalis adults were used in fecundity study. The laid eggs were observed daily and longevity of adults were recorded. Standard life table parameters and population age structures were calculated from daily records of survival, mortality and fecundity of each cohort. Two-sample t-test was performed in comparing of longevity between adult male and female. The highest mortality was recorded in first instar larvae (22.58%) with K-value of 0.125 indicated that this stage is the key factor in regulating C. medinalis population. A total of 32.26% individuals has successfully reached at adult stage with average sex ratio was 0.96:1.00 (Female: Male). The emergence of first female was on day 28 whilst the last female died on day 43. The earliest egg was laid on day 30 and continued until day 35 with maximum oviposition was on day 31 and 32 which constitute 57.04% of total eggs. The female lived for about 7.56±0.38 days with fecundity of 104.33±5.43 eggs. The intrinsic rate of natural increase (rm) was 0.08 per female per day with mean generation time (Tc) of 31.56 days and doubling time (DT) of 8.19days. This shows that C. medinalis population has increased and build up rapidly in short time period. Our results suggested that the control program should be done during early stage of larvae in order to suppress the C. medinalis population effectively. Life table study of C. medinalis on other local rice varieties should be conducted in determining its survivorship and reproduction on other host varieties.